A Protocol for Mitotic Metaphase Chromosome Count Using Shoot Meristematic Tissues of Mulberry Tree Species - Raju Mondal; Sreya Antony; Belaghihalli Gnanesh; G Thanavendan; G. Ravikumar; B Sreenivasa; S. Gandhi Doss; K Vijayan (Bio-Protocol, 2023)
Studies on chromosomal status are a fundamental aspect of plant cytogenetics and breeding because changes in number, size, and shape of chromosomes determine plant physiology/performance. Despite its significance, the classical cytogenetic study is now frequently avoided because of its tedious job. In general, root meristems are used to study the mitotic chromosome number, even though the use of root tips was restricted because of sample availability, processing, and lack of standard protocols. Moreover, to date, a protocol using shoot tips to estimate chromosome number has not yet been achieved for tree species’ germplasm with a large number of accessions, like mulberry (Morus spp.). Here, we provide a step-by-step, economically feasible protocol for the pretreatment, fixation, enzymatic treatment, staining, and squashing of meristematic shoot tips. The protocol is validated with worldwide collections of 200 core set accessions with a higher level of ploidy variation, namely diploid (2n = 2x = 28), triploid (2n = 3x = 42), tetraploid (2n = 4x = 56), hexaploid (2n = 6x = 84), and decosaploid (2n = 22x = 308) belonging to nine species of Morus spp. Furthermore, accession from each ploidy group was subjected to flow cytometry (FCM) analysis for confirmation. The present protocol will help to optimize metaphase plate preparation and estimation of chromosome number using meristematic shoot tips of tree species regardless of their sex, location, and/or resources.